2010
DOI: 10.1177/009318531003800306
|View full text |Cite
|
Sign up to set email alerts
|

Common Errors in the Assessment of Allegations of Child Sexual Abuse

Abstract: The assessment of child sexual abuse (CSA) allegations is a complex, challenging, high-stakes undertaking. The consequences of sloppy assessments leading to false positive or false negative court decisions are clearly severe. Despite this, many professionals and paraprofessionals who undertake such assessments continue to perform substandard child sexual abuse investigations. This article presents some of the common errors made by CSA investigators and suggests the use of research-based investigative protocols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Forensic interviewing, a means of gathering factual information from a CSA survivor or witness about abuse for use in a legal setting in a legally defensible and developmentally appropriate manner, is frequently essential to the conduction of CSA investigations, as the survivor and alleged perpetrator may be the only people who know details of what really happened. 8 , 9 Interviews are conducted by individuals who are skilled in child development, linguistics, civil and criminal offenses, memory, and suggestibility using a nationally recognized and approved forensic interview process. These FIs, which are performed in a safe, child-friendly, neutral setting, provide a unique opportunity for the survivor to share specific details regarding their abuse experience that may impact investigation and prosecutorial trajectory and the safety of other children and adolescents around them (such as through the identification of other abuse survivors and/or perpetrators).…”
Section: Approach To Assessing and Treating Child Sexual Abuse At The...mentioning
confidence: 99%
“…Forensic interviewing, a means of gathering factual information from a CSA survivor or witness about abuse for use in a legal setting in a legally defensible and developmentally appropriate manner, is frequently essential to the conduction of CSA investigations, as the survivor and alleged perpetrator may be the only people who know details of what really happened. 8 , 9 Interviews are conducted by individuals who are skilled in child development, linguistics, civil and criminal offenses, memory, and suggestibility using a nationally recognized and approved forensic interview process. These FIs, which are performed in a safe, child-friendly, neutral setting, provide a unique opportunity for the survivor to share specific details regarding their abuse experience that may impact investigation and prosecutorial trajectory and the safety of other children and adolescents around them (such as through the identification of other abuse survivors and/or perpetrators).…”
Section: Approach To Assessing and Treating Child Sexual Abuse At The...mentioning
confidence: 99%
“…Thus, the sooner child abuse is discovered, the better for the prevention of re-abuse and treatment of the negative consequences of child abuse. Since child abuse often happens behind closed doors and forensic-technical evidence is limited, the child forensic interview is crucial to find out what happened (e.g., Mart, 2010). Knowledgeable professionals that conduct proper child forensic interviews are therefore needed to prevent errors in the approach of alleged child abuse cases and create optimal conditions for children to tell their story about what happened to them.…”
Section: Suggestive Questions Misinformation and The Formation Of Fal...mentioning
confidence: 99%
“…The Risk-Need-Responsivity (RNR) model states that in order to reduce the chance of harmful behavior in the future, the relevant, modifiable (dynamic) risk factors need to be addressed (Andrews & Bonta, 2007;2010). Static risk factors are immutable (for example: showed that in the files of the former Child Abuse Advice and Reporting Centers (CAARC;…”
Section: Risk Assessment In Child Abuse Casesmentioning
confidence: 99%